An Integrative Computational Approach for the Identification of C-Abl Kinase Inhibitors from Anti-Parkinson Plant-Derived Bioactive - Umar, Haruna Isiyaku; Ashimiyu-Abdusalam, Zainab; Kumar, Neeraj; Kuthi, Najwa Ahmad; Victor, Omoboyede; Abdulsalam, Zainab Naeem; Aribo, Elizabeth Oluwabunmi; Bello, Ridwan Opeyemi; Jardan, Yousef A. Bin; Nafidi, Hiba-Allah; Bourhia, Mohammad (Medicinal Chemistry, 2025)
BackgroundOxidative stress is strongly linked to neurodegeneration through the activation of c-Abl kinase, which arrests α-synuclein proteolysis by interacting with parkin interacting substrate (PARIS) and aminoacyl tRNA synthetase complex-interacting multifunctional protein 2 (AIMP2). This activation, triggered by ataxia-telangiectasia mutated (ATM) kinase, leads to dopaminergic neuron loss and α-synuclein aggregation, a critical pathophysiological aspect of Parkinson’s disease (PD). To halt PD progression, pharmacological inhibition of c-Abl kinase is essential. Despite three generations of tyrosine kinase inhibitors (TKIs) being explored for PD treatment, they present significant concerns including poor blood-brain barrier penetration, off-target effects, and severe side effects. Notably, there are currently no FDA-approved c-Abl kinase inhibitors in clinical usage for PD treatment, highlighting the urgent need for potent, safe, and cost-effective alternatives.ObjectiveThis study aims to identify potential c-Abl kinase inhibitors from plant-derived compounds with reported anti-Parkinson's potential and their derivatives using molecular docking, molecular dynamics simulations (MDS), and in silico pharmacokinetics and toxicity profiling.MethodsSeventy-eight compounds sourced from literature were docked against c-Abl kinase using Maestro 12.5. The top three hit compounds, along with nilotinib (control drug), were subjected to drug-likeness, ADMET profiling using the AI Drug Lab server and 100 ns MDS using Desmond.ResultsAmburoside A, diarylheptanoid MS13, and dimethylaminomethyl-substituted-curcumin showed binding affinities close to nilotinib, with values of -12.615, -12.556, and -11.895 kcal/mol respectively, compared to nilotinib's -16.826 kcal/mol. The three plant-derived compounds exhibited excellent structural stability and favorable ADMET profiles, including optimal blood-brain barrier permeation.ConclusionThe three hit compounds identified in this study show potential as c-Abl kinase inhibitors. Given the absence of FDA-approved c-Abl kinase inhibitors for PD, these findings are significant as they could contribute new therapeutic options for the treatment and management of PD. However, further in vitro and in vivo experiments are necessary to validate these findings.
Keywords: c-abl kinase